Technological Capability Growth and Performance Outcome: Foreign versus Local Firms in China. Issue 2 (June 2013) - Ju, Min; Zhou, Kevin Zheng; Gao, Gerald Yong; Lu, Jiangyong
This study examines the growth and performance impact of technological capability (TC) in China. The authors posit that foreign and local firms exhibit different TC growth patterns and that TC has differential performance effects for these two types of firms. From a multilevel analysis of five-year panel data of 448 technology-oriented firms, they find that, in general, foreign firms possess higher levels of TC, whereas local firms can develop their TC faster than foreign firms. Furthermore, compared with foreign firms, local firms experience a stronger performance return from their TC; however, foreign firms have a higher growth rate in the contribution of TC to their performance over time. Moreover, firms can develop TC faster in regions with better intellectual property protection, and TC exerts a stronger effect on performance when industrial uncertainty is higher.